Ergonomic Interventions for Preventing Musculoskeletal Disorders among Nurses: A Systematic Review in Occupational Health Settings - Asri Sukmaning Tias; Desiyani Nani (Universitas Muhammadiyah Semarang, 2026)
Musculoskeletal disorders (MSDs) are a major occupational health concern among nurses, contributing to pain, disability, absenteeism, and increased healthcare costs. This systematic review aimed to evaluate the effectiveness of ergonomic interventions in preventing MSDs among nurses and to identify key implementation factors. The review followed PRISMA 2020 guidelines. A systematic search was conducted across four databases (Scopus, PubMed, ScienceDirect, and CINAHL) for studies published between 2019 and 2025. Randomized controlled trials and quasi-experimental studies were included, and methodological quality was assessed using the Joanna Briggs Institute (JBI) checklist. Due to heterogeneity in interventions and outcomes, findings were synthesized narratively. Ten studies involving 1,875 nurses were included. Multimodal ergonomic interventions combining training, assistive devices, and organizational support demonstrated the strongest effects. Equipment-based interventions significantly reduced back injuries when compliance was high, while educational programs improved ergonomic knowledge with variable clinical outcomes. Technology-assisted interventions showed promising results in reducing MSD incidence. Overall, ergonomic interventions are effective in reducing MSD risk among nurses, particularly when implemented through comprehensive and well-supported programs. Organizational readiness and resource availability are critical for successful implementation. Future research should focus on long-term outcomes and implementation strategies.